Reaktualisasi Etika Islam terhadap Lingkungan: (Sebuah Upaya Penanggulangan Krisis Global Perspektif Islam) - Mutrofin (Prodi Sosiologi Agama, 2019)
This article reviews the Industrial Revolution that occurred in the 18th century had an impact on the acceleration of natural destruction. Bald forests, river bribery, and so on indicate an unbalanced relationship between humans and the environment. The global crisis often leads to disasters such as landslides, floods, forest fires, droughts and more. Various damage that occurs is none other than because of human activities that treat nature arbitrarily. In fact, Islam teaches its people to continuously maintain and maintain the universe. Efforts to re-actualize the ethics of Islam to the environment can run optimally with some principles of environmental management taught in Islam. These principles are used as the basis for tackling the current global crisis so that the balance between humans and the environment will be realized.